Progression of brain atrophy in the early stages of Parkinson's disease: A longitudinal tensor‐based morphometry study in de novo patients without cognitive impairment. Issue 8 (22nd January 2014) - Tessa, Carlo; Lucetti, Claudio; Giannelli, Marco; Diciotti, Stefano; Poletti, Michele; Danti, Sabrina; Baldacci, Filippo; Vignali, Claudio; Bonuccelli, Ubaldo; Mascalchi, Mario; Toschi, Nicola
Abstract: The presence of brain atrophy and its progression in early Parkinson's disease (PD) are still a matter of debate, particularly in patients without cognitive impairment. The aim of this longitudinal study was to assess whether PD patients who remain cognitively intact develop progressive atrophic changes in the early stages of the disease. For this purpose, we employed high‐resolution T1‐weighted MR imaging to compare 22 drug‐naïve de novo PD patients without cognitive impairment to 17 age‐matched control subjects, both at baseline and at three‐year follow‐up. We used tensor‐based morphometry to explore the presence of atrophic changes at baseline and to compute yearly atrophy rates, after which we performed voxel‐wise group comparisons using threshold‐free cluster enhancement. At baseline, we did not observe significant differences in regional atrophy in PD patients with respect to control subjects. In contrast, PD patients showed significantly higher yearly atrophy rates in the prefrontal cortex, anterior cingulum, caudate nucleus, and thalamus when compared to control subjects. Our results indicate that even cognitively preserved PD patients show progressive cortical and subcortical atrophic changes in regions related to cognitive functions and that these changes are already detectable in the early stages of the disease. Hum Brain Mapp 35:3932–3944, 2014 . © 2014 Wiley Periodicals, Inc .